2019
DOI: 10.1016/j.ajhg.2019.05.017
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing and Reanalyzing the Genome: Findings from the MedSeq Project

Abstract: Although genome sequencing is increasingly available in clinical and research settings, many questions remain about the interpretation of sequencing data. In the MedSeq Project, we explored how much effort is required to evaluate and report on more than 4,500 genes reportedly associated with monogenic conditions, as well as pharmacogenomic (PGx) markers, blood antigen serotyping, and polygenic risk scores in 100 individuals (50 with cardiomyopathy and 50 healthy) randomized to the sequencing arm. We defined th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 45 publications
1
44
0
Order By: Relevance
“…Studies have also proven that periodic reanalysis of the data in individuals not diagnosed on initial testing could improve the diagnostic yield. 31,32 However, in the study by Lynch et al, 8 resequencing the negative patients with whole exome did not improve the diagnostic yield. It is also emphasized that a negative result should always prompt the physician to pursue alternate diagnostic approaches if the phenotype is convincing.…”
Section: Discussionmentioning
confidence: 90%
“…Studies have also proven that periodic reanalysis of the data in individuals not diagnosed on initial testing could improve the diagnostic yield. 31,32 However, in the study by Lynch et al, 8 resequencing the negative patients with whole exome did not improve the diagnostic yield. It is also emphasized that a negative result should always prompt the physician to pursue alternate diagnostic approaches if the phenotype is convincing.…”
Section: Discussionmentioning
confidence: 90%
“…While the patients consented to participate in this pilot study knowing that results would not be returned to them or their physicians, these data inform the complexity of returning genetic results generated in a research setting to diverse participants. Consistent with the MedSeq Project [17], which performed whole genome sequencing on cardiomyopathy patients and healthy participants, approximately 20% of the present study population would be receiving results for one to two pathogenic ClinVar two-star variants. All 130 participants would receive research results if ClinVar-designated pathogenic or likely pathogenic variants of all levels of evidence are to be returned.…”
Section: Resultsmentioning
confidence: 73%
“…Also, variant classification and interpretation can change over time as more data are collected. ClinVar is not a static database [37], and information relayed in a static report issued to a participant could quickly become outdated [17]. Here, we observed that 45% of one-star pathogenic variants from an earlier version of ClinVar were upgraded to two-star pathogenic or likely pathogenic in a 2019 version of ClinVar.…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…This contrasts with the 1-4 hours we typically require for an ES/GS research analysis to identify candidate variants and manually inspect the transcriptome for abnormalities. In one recent report, the time required was up to 6-8 hours for genome analysis (14). The following are several case examples of this approach in making diagnoses that also show the limitations of commonly used diagnostic tests.…”
Section: Resultsmentioning
confidence: 99%